Web-дизайн, як поєднання психології та мультимедіа - Гречко, А. В.; Колендовська, М. М. (ХНУРЕ, 2022)
This article discusses several basic concepts of psychology used in interface design and web resources. Brief examples of the use of these concepts are given. Visual cues, Gestalt principles, short-term memory, the concept of motivation, and the concept of examples are just a few examples of how psychology influences web resource design. Psychology helps in choosing fonts, color palette and creating a website framework. Drawing up a portrait of the user and testing the prototype also do not do without the basics of psychology. Describes why a skilled web designer and designer should learn today.